Implementasi Etika Bisnis Islam Pada Pedagang di Pasar Kelurahan Kelayu Selatan Kecamatan Selong Kabupaten Lombok Timur - Dini Ismayanti; Akhmad Jufri; Moh. Huzaini (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This research aims to understand the comprehension and implementation of Islamic business ethics by traders in the Kelayu Selatan market. This study employs a qualitative approach descriptive method. Data collection techniques used include observation, interviews, and documentation. The determination of informants uses purposive and snowball techniques. The data validity method used is triangulation. The data analysis follows the Miles and Huberman interactive model, comprising data collection, data reduction, data presentation, and conclusion drawing. The research result indicate that the majority of traders in the Kelayu market are fully aware of and understand the Islamic business ethics taught by Prophet Muhammad SAW. Ttraders have implemented these ethics by being honest, trustworthy, transparent, and innovative. In terms of honesty, traders do not use oaths and are truthful in measurements. Regarding trustworthiness, traders do not break promises, never hoard goods, set transparent prices, and have not fully maintained specific records of debtors. In terms of transparency, traders always provide information about the goods they sell, offer good services, and are willing to negotiate with buyers. Lastly, traders use strategies in trading, maintain good relationships, and regularly provide discounts.